Evaluation of pulmonary functions in pediatric patients with beta-thalassemia major - Lotfy Abdelfattah Elsehaimy; Mokhles Abdel Fadil Zineldin; Wafaa Alsaed Khalil (Wolters Kluwer Medknow Publications, 2019)
Background Thalassemia is a challenging health problem all over the world, especially in Mediterranean areas. Its effect on pulmonary function has not been well studied. Aim of the work To describe pulmonary function changes in patients with β-thalassemia major. Patients and methods This study included 60 patients with β-thalassemia major who received regular blood transfusion (40 males and 20 females) and 30 control children (20 males and 10 females). All participants were subjected to full history taking, clinical examination, and laboratory investigations (complete blood count, serum iron, and serum ferritin). In addition, all underwent pulmonary function tests. Results Forced expiratory volume at first second, forced vital capacity, and forced expiratory flow 25-75% were significantly decreased in males and females in the patient group when compared with those in the control group. However, forced expiratory volume at first second/forced vital capacity was significantly increased in male and female patients when compared with those in the control group. Transfusion and chelation therapy seems to be the cause of reduced pulmonary function. Conclusion Children with β-thalassemia had reduced pulmonary function, and this could be attributed to chelation therapy that affects serum iron and ferritin.